Simultaneous investigation of cardiac pyruvate dehydrogenase flux, Krebs cycle metabolism and pH, using hyperpolarized [1,2- C ]pyruvate in vivo - Chen, A; Hurd, R; Schroeder, M; Lau, A; Gu, Y; Lam, W; Barry, J; Cunningham, C; Tropp, J (2012)
C MR spectroscopy studies performed on hearts ex vivo and in vivo following perfusion of prepolarized [1- C]pyruvate have shown that changes in pyruvate dehydrogenase (PDH) flux may be monitored non-invasively. However, to allow investigation of Krebs cycle metabolism, the C label must be placed on the C2 position of pyruvate. Thus, the utilization of either C1 or C2 labeled prepolarized pyruvate as a tracer can only afford a partial view of cardiac pyruvate metabolism in health and disease. If the prepolarized pyruvate molecules were labeled at both C1 and C2 positions, then it would be possible to observe the downstream metabolites that were the results of both PDH flux ( CO and H CO ) and Krebs cycle flux ([5- C]glutamate) with a single dose of the agent. Cardiac pH could also be monitored in the same experiment, but adequate SNR of the CO resonance may be difficult to obtain in vivo. Using an interleaved selective RF pulse acquisition scheme to improve CO detection, the feasibility of using dual-labeled hyperpolarized [1,2- C ]pyruvate as a substrate for dynamic cardiac metabolic MRS studies to allow simultaneous investigation of PDH flux, Krebs cycle flux and pH, was demonstrated in vivo. © 2011 John Wiley and Sons, Ltd.